Penerapan Aromaterapi Lemon (Citrus) Pada Penurunan Nyeri Menstruasi Mahasiswi Program Studi DIII Keperawatan Semester 6 Universitas ‘Aisyiyah Surakarta - Afnani Salma Bayyinah; Hermawati Hermawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Menstrual pain in the world is very high, 50% of women worldwide, Bulgaria 8.8%, Finland 94% while Indonesia 64.25%. Menstrual pain causes short and long term adverse effects including interference with daily activities and even an increase in absenteeism at the campus, long-term effects cause tissue growth outside the uterus. Menstrual pain can be treated with pharmacological and non-pharmacological therapies. One of the non-pharmacological therapies is inhaling lemon aromatherapy. Limeone contains lots of vitamin C which will control prostaglandins and reduce pain. Objective: To describe the results before and after the application of lemon aromatherapy on reducing menstrual pain. Methods: Case study with descriptive design on 2 respondents who were given lemon aromatherapy for 15 minutes twice a day for 2 days, and measured using Numeric Rating Scale. Results: After lemon aromatherapy was performed on both respondents with menstrual pain, it showed a decrease in the pain scale from moderate pain to mild pain. Conclusion: The application of lemon aromatherapy can reduce menstrual pain in female students from moderate to mild